Architectural Integration of Augmented Reality: A Review of System Architectures, Implementation Barriers, and Design-Driven Application Strategies - Xiao, Lin; Mokhtar, Noor Aisyah; Mat Sulaiman, Mohd Khairul Azhar (RUAS, 2025)
The integration of Augmented Reality (AR) into the Architecture, Engineering, and Construction (AEC) industry offers transformative potential, yet its practical adoption remains fragmented across different design phases. This study presents a comprehensive review of architectural AR systems, analyzing developments from 2008 to 2024. Employing a PRISMA-informed semi-systematic protocol, the research synthesized data from Web of Science, Scopus, and Google Scholar, supplemented by backward and forward snowballing techniques. Through thematic analysis, the review identifies four distinct AR system typologies and examines their integration with Building Information Modelling (BIM), Internet of Things (IoT), and Geographic Information Systems (GIS). The findings reveal that despite technical advancements, significant barriers persist, particularly regarding hardware limitations, authoring complexity, and organizational resistance to new workflows. To address these impediments, the study highlights emerging design-driven solutions, including the adoption of cloud-based architectures, modular component libraries, and real-time on-site overlays. Based on these insights, the paper proposes a strategic framework for future development, advocating for seamless interoperability and user-centred interfaces. Ultimately, this research argues for a paradigm shift, positioning AR not merely as a visualization novelty, but as a critical, data-integrated tool capable of enhancing decision-making and collaborative processes throughout the architectural lifecycle.